THE LINGUISTIC LANDSCAPE OF SENIOR HIGH SCHOOLS IN SINGARAJA: ANALYZING THE LANGUAGE USE AND CHARACTER EDUCATION VALUES ON SCHOOL SIGNS - Kadek Danny Brahmantara Putra; Made Suta Paramarta; Amanda Vira Maharani (Undiksha Press, 2026)
The linguistic landscape in school environments is expected to systematically integrate multilingual representation, effective syntactic construction, meaningful themes, and character education values; however, existing school signage often emphasizes language visibility without comprehensively reflecting educational and moral dimensions. This study aims to critically analyze and interpret the distribution of languages and scripts, evaluate syntactic units, examine thematic patterns, and synthesize the representation of character education values embedded in senior high school signage. The research employed a qualitative descriptive design. The subjects consisted of two senior high schools with 12 informants, including 2 principals, 4 teachers, and 6 students, and 258 public signs as the primary data source. Data were collected through structured observation, documentation using analysis sheets, and semi-structured interviews validated through content validity procedures. Data analysis followed the interactive model of condensation, data display, and conclusion drawing with triangulation to ensure credibility. The findings reveal that Indonesian predominates as the primary informative language, while English and Balinese script function symbolically; syntactic units are strategically selected with text and phrase forms most frequent; themes emphasize attitudes, discipline, and environmental awareness; and character values such as responsibility, social care, and discipline are most prominently represented. In conclusion, school signage functions as a strategic communicative resource that reflects language policy implementation and reinforces institutional character education priorities. The study implies that educational institutions can optimize linguistic landscapes as structured pedagogical tools to strengthen multilingual awareness and value-based school culture.